СИСТЕМА ОХОРОНИ ЗДОРОВ’Я В УМОВАХ ІНСТИТУЦІЙНИХ ЗМІН В УКРАЇНІ: ФІНАНСОВІ АСПЕКТИ (Світ фінансів, 2017)
Музика І. С., Возняк Г. В. Система охорони здоров’я в умовах інституційних змін в Україні: фінансові аспекти. Розглянуто питання функціонування та фінансового забезпечення системи охорони здоров’я в Україні. Проаналізовано ключові аспекти, пов’язані зі зміною підходів і механізмів фінансування цієї галузі у контексті бюджетної децентралізації та реформи місцевого самоврядування і територіальної організації влади в країні. Наголошено на неефективності інституту субвенцій, позаяк за своїм змістом та формою він не є соціально дієвим та не враховує реальних потреб регіонів. Виокремлено проблеми, пов’язані з оптимізацією мережі закладів охорони здоров’я та надання їм фінансової автономії. На основі проведеного аналізу доведено необхідність проведення подальших реформ, які покликані змінити “філософію” фінансування системи охорони здоров’я. Музыка И. С., Возняк Г. В. Система здравоохранения в условиях институциональных изменений в Украине: финансовые аспекты. Рассмотрены вопросы функционирования и финансового обеспечения системы здравоохранения в Украине. Проанализированы ключевые аспекты, связанные с изменением подходов и механизмов финансирования данной отрасли в контексте бюджетной децентрализации, реформы местного самоуправления и территориальной организации власти в стране. Сделан акцент на неэффективности института субвенций, поскольку по своему содержанию и форме он не является социально действенным и не учитывает реальных потребностей регионов. Выделены проблемы, связанные с оптимизацией сети учреждений здравоохранения и предоставления им финансовой автономии. На основе проведенного анализа доказана необходимость проведения дальнейших реформ, призванных изменить “философию” финансирования системы здравоохранения. Muzyka I., Voznjak H. The healthcare system in the context of institutional changes in Ukraine: financial aspects. Introduction. Under reform of local government and territorial authority management in Ukraine, main relevance has the questions about functioning and financial assurance of the healthcare system. Intense interest to this topic is caused by not only the healthcare system management in Ukraine but also by growing demands of the patients for the quality of medical services. Take into account multidimensionality of these phenomenon questions of impact analysis and ways of improving financial mechanism of the healthcare system become actual.Purpose of this article is an analysis and an assessment of the condition of the financial assurance of the healthcare system in the context of institutional changes in Ukraine.Results. In this article the questions about functioning and financial assurance of the healthcare system in Ukraine are discussed. Was conducted a problem oriented analysis of the key aspects, associated with changing approaches and financial mechanisms of this branch in a context of fiscal decentralization and local government reform and territorial authority management in the country. Has been analyzed a budget spending on healthcare (different levels of the budget). Is mentioned an inefficiency of institute subvention, because its content and form is not very effective and it doesn’t take into account the real needs of the regions. Separately emphasized the problems related to optimization of healthcare institutions and providing them with financial autonomy.Conclusion. As the result of the research authors explain the need for further reforms that will change “the philosophy” of funding of the healthcare system. It is shown that the existing financial mechanism (rendering medical subvention to local budgets) doesn’t take into account specifics of the regions, which means it requires improving the formula of calculation of medical subvention for the future.